The World Bank is using International Food Policy Research Institute research results to enhance the nutrition outcomes of irrigation investments in sub-Saharan Africa - CGIAR Research Program on Water, Land and Ecosystems (2021)
Since 2013, researchers at the International Food Policy Research Institute (IFPRI) have generated evidence of the relationship between small-scale irrigation and nutrition to fill an important research gap. The World Bank approached IFPRI to develop guidance, drawing on this research. The guidance highlights the pathways through which irrigation improves nutrition, intervention options, and indicators to measure food security and nutrition outcomes. It informed the design of two projects in Uganda and Tanzania and will be scaled out to other projects.